Pengaruh Metode Scrambel Terhadap Hasil Belajar pada Mata Pelajaran PKN di Kelas V MIS Al-Imam Klumpang Tahun Ajaran 2022/2023 - Yuslina, Elma (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study aims to investigate the relationship between the use of paper puppet media and students’ learning motivation in Social Studies subjects among fifth-grade students at MIS Al-Imam Klumpang during the 2022/2023 academic year. This research employs a quantitative approach using the descriptive analytical research method as developed by Sumadi Suryabrata (2013). The study involves 25 students, comprising 8 males and 17 females. The independent variable is the use of paper puppet media, while the dependent variable is students' learning motivation. The study was conducted in a single action cycle consisting of three stages: planning, implementation and observation, and reflection. Data were collected through observations, questionnaires, and documentation, and analyzed using the Pearson Product-Moment correlation test. The results indicate a significance value of 0.068, which exceeds the threshold of 0.05, suggesting that there is no statistically significant relationship between the use of paper puppet media and students' learning motivation in Social Studies. These findings imply that other factors may have a more substantial influence on students' learning motivation, necessitating to explore alternative instructional strategies.